The Relatonship Of Characteristics and Participation of Kkpa Members Toward The Cooperative Unit Village (Kud) Sumber Rezeki in Buluh Rampai Seberida District of Indragiri Hulu Regency - Ningsih, Rofikhoh Tias; Yulida, Roza; ', Cepriadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research was (1) the characteristic of KKPA member toward cooperative unit village (KUD) Sumber Rezeki, (2) the participation of KKPAÂ  member toward KUD, (3) the relationship of characteristic and participation of KKPA member toward cooperative unit village (KUD) in Buluh Rampai Seberida district of Indragiri Hulu regency. The method used was survey method where the population of this research was the members of cooperative at Buluh Rampai the total of KKPA member 597 which classified into 32 groups. The technique of collecting data used simple random sampling system which taken one of 32 respondents with criteria included the member of KKPA . The result of this research was the significant relationship of characteristic and participation of KKPA member toward the cooperative unit village (KUD) in Buluh Rampai Seberida district of Indragiri Hulu regency. Â  Keyword : characterstic, participation, significant, unit coperatives village, KKPA